Nanocellulose coated paper diagnostic to measure glucose concentration in human blood - Hossain, Laila; De Francesco, Marisa; Tedja, Patricia; Tanner, Joanne; Garnier, Gil (Frontiers in Bioengineering and Biotechnology, 2022)
A new generation of rapid, easy to use and robust colorimetric point of care (POC) nanocellulose coated-paper sensors to measure glucose concentration in blood is presented in this study. The cellulose gel containing the enzyme with co-additive is coated and dried onto a paper substrate. Nanocellulose gel is used to store, immobilize and stabilize enzymes within its structure to prolong enzyme function and enhance its availability. Here, we immobilize glucose oxidase within the gel structure to produce a simple colorimetric blood glucose sensor. Increase in blood glucose concentration increases the concentration of reaction product which decreases the system pH detected by the pH indicative dye entrapped in the nanocellulose gel. The sensor produces a color change from red to orange as pH decreases due to the enzymatic reaction of glucose into gluconic acid and hydrogen peroxide. This sensor can measure glucose concentrations of 7-13 mM (medical range for diabetes control) at temperatures of 4 °C to 40 °C. Stability tests confirm that no denaturation of enzyme occurs by measuring enzyme activity after four weeks. A prototype device is designed to instantly measure the glucose concentration from blood in a two steps process: (i) red blood cell separation and (ii) quantification of glucose by color change. This study demonstrates nanocellulose sensor as an economical, robust, and sensitive diagnostic technology platform for a broad spectrum of diseases.